Effect of Exercise on Breast Cancer: A Systematic Review and Meta-analysis of Animal Experiments - Li, Yuxi; Xiao, Xili; Zhang, Yue; Tang, Wenjing; Zhong, Dongling; Liu, Tianyu; Zhu, Yuanyuan; Li, Juan; Jin, Rongjiang (Frontiers in Molecular Biosciences, 2022)
Objective Exercise is considered to be beneficial for breast cancer. However, the results seem inconsistent. We conducted this systematic review and meta-analysis of animal experimental studies to fully understand the effect of exercise on breast cancer in mice. Method We searched databases from inception to April 2022 and manually searched related references to retrieve eligible studies. We screened eligible studies and extracted related data. We assessed the methodological quality and reporting quality and summarized the study characteristics and findings of included studies. We conducted meta-analysis with RevMan software. Subgroup analysis and sensitivity analysis were also performed. Results We identified 366 potential literatures and included 46 articles for analysis. In methodological quality assessment, only selective outcome reporting was in low risk of bias, three items were rated with high risk of bias, and most of other items were rated unclear risk of bias. In reporting quality assessment, low reporting rate was observed in 5 items. Meta-analysis showed that, compared with sedendary group, exercise reduced more tumor weight and tumor number per animal. Exercise decreased more tumor incidence than sedentary both in motorized wheel/high-intensity and free wheel/low-intensity treadmill running. Sensitivity analysis showed that the results were robust. Conclusion Exercise could reduce tumor weight, number of tumors per animal, and incidence of tumor in breast cancer model of mice. However, the methodological standard and reporting guidelines in preclinical studies should be concerned.